First‐in‐man study of Heartech® percutaneous left ventricular partitioning device for treatment of heart failure postmyocardial infarction. Issue 6 (23rd June 2019) - Zhu, Zhengbin; Yu, Jiwei; Xu, Kai; Tang, Yimin; Fang, Yuehua; Gu, Jianing; Gu, Shengjia; Ding, Fenghua; Modine, Thomas; Zhang, Ruiyan
Abstract: Objective: This first‐in‐man (FIM) study aimed to determine the safety and efficacy of the Heartech® left ventricular partitioning device (LVPD) in patients with chronic heart failure (HF) postmyocardial infarction. Methods: Sixteen patients were enrolled from three cardiac intervention centers in China. All patients underwent percutaneous ventricular restoration (PVR) procedures with implantation of the Heartech® LVPD. Safety and immediate success rates were recorded. Major adverse cardiovascular and cerebrovascular events (MACCEs) including all‐cause mortality, myocardial infarction, stroke, emergent or selective surgery or interventional therapy, renal failure requiring hemodialysis, and major bleeding were recorded. Efficacy features included functional status, echocardiographic characteristics, life quality characteristics including peak oxygen consumption of cardiopulmonary exercise testing (CPET), European five‐dimensional health scale (EQ‐5D), 6‐min walk test (6MWT) at baseline and during follow‐up (NCT 02938637). Results: The device success rate was 93.75% (15 successes in 16 patients) with 100% safety. During follow‐up of 36 ± 4.5 days, no MACCEs were found. The left ventricular end‐systolic volume index decreased significantly (LVESVi, 72.47 ± 22.77 mL/m 2 vs. 50.13 ± 13.36 mL/m 2, p  < .001) as did left ventricular end diastolic volume index (LVEDVi, 106.27 ± 28.01 mL/m 2 vs. 83.20 ± 16.87 mL/m 2, p = .001). Left ventricular ejection fraction (LVEF, 32.47 ± 6.98% vs. 40.41 ± 6.15, p  < .001), 6MWT (383.13 ± 108.70 vs. 453.47 ± 88.24, p < 0.001) and EQ‐5D (65.93 ± 11.25 vs. 78.67 ± 8.35, p  < .001) improved significantly. Conclusions: Heartech® LVPD appeared to be safe and effective for treatment of HF postmyocardial infarction.